Many-body van der Waals interactions in multilayer structures studied by atomic force microscopy - Xiao Wang; Zepu Kou; Ruixi Qiao; Yuyang Long; Baowen Li; Xuemei Li; Wanlin Guo; Xiaofei Liu; Jun Yin (Nature Communications)
Abstract Van der Waals interaction in multilayer structures was predicted to be of many-body character, almost in parallel with the establishment of Lifshitz theory. However, the diminishing interaction between layers separated by a finite-thickness intermediate layer prevents experimental verification of the many-body nature. Here we verify the substrate contribution at the adhesion between the atomic force microscopy tip and the supported graphene, by taking advantage of the atomic-scale proximity of two objects separated by graphene. While the pairwise dispersion theory overestimates the substrate contribution at critical adhesive pressures, the many-body dispersion theory remedies this deficiency, highlighting the non-additivity nature of substrate contribution. The many-body effect is further understood through the energy spectrum of charge density fluctuations. These findings open the door to modulating the van der Waals interaction on two-dimensional material surfaces, which would be relevant to various technologies, including microelectromechanical systems and surface molecular assembly.